Context Matters: A Qualitative Synthesis of Adherence Literature for People on Hemodialysis. Issue 1 (28th January 2023) - Taylor, Kathryn S.; Umeukeje, Ebele M.; Santos, Sydney R.; McNabb, Katherine C.; Crews, Deidra C.; Hladek, Melissa D.
Abstract : Abstract : Key Points: Qualitative research that explores hemodialysis patient perspectives about adherence may point to gaps in existing adherence interventions. Patients' goals included balancing treatment and competing priorities, preserving a sense of their "old selves, " and minimizing symptoms. Adherence may improve when clinicians routinely elicit patients' goals and partner to resolve conflicts between those goals and adherence. Background: Patients with ESKD treated with hemodialysis in the United States have persistently higher rates of nonadherence compared with patients in other developed countries. Nonadherence is associated with an increased risk of death and higher medical expenditure. There is an urgent need to address it with feasible, effective interventions as the prevalence of patients on hemodialysis in the United States continues to grow. However, published adherence interventions demonstrate limited long-term efficacy. Methods: We conducted a synthesis of qualitative studies on adherence to hemodialysis treatment, medications, and fluid and dietary restrictions to identify gaps in published adherence interventions, searching PubMed, CINAHL, PsychInfo, Embase, and Web of Science databases. We analyzed qualitative data with a priori codes derived from the World Health Organization's adherence framework and subsequent codes from thematic analysis. Results: We screened 1775 articles and extracted qualitative data from 12. The qualitative data revealed 20 factors unique to hemodialysis across the World Health Organization's five dimensions of adherence. In addition, two overarching themes emerged from the data: ( 1 ) adherence in the context of patients' whole lives and ( 2 ) dialysis treatment as a double-edged sword. Patient-level factors reflected in the qualitative data extended beyond knowledge about hemodialysis treatment or motivation to adhere to treatment. Patients described a profound grieving process over the loss of their "old self" that impacted adherence. They also navigated complex challenges that could be exacerbated by social determinants of health as they balanced treatment, life tasks, and social roles. Conclusions: This review adds to the growing evidence that one-size-fits-all approaches to improving adherence among patients on hemodialysis are inadequate. Adherence may improve when routine care incorporates patient context and provides ongoing support to patients and families as they navigate the logistical, physical, and psychological hardships of living with dialysis. New research is urgently needed to guide a change in course.